Soft embalming of cadavers for training purposes: Optimising for long-term use in tropical weather - Raghuveer Reddy; Subramania Iyer; Minnie Pillay; Krishnakumar Thankappan; Janarthanan Ramu (Indian Journal of Plastic Surgery)
Background: Surgical and anatomical training has been found to be most optimally simulated in a cadaver than any other available methods. Soft embalming methods have made the bodies more ‘lifelike’ and better suited for training. The widely accepted soft embalming techniques, including Thiel embalming, are designed for temperate climates. Their use in tropical locations has been found to be associated with poor short-term and long-term preservation of the bodies. In fact, adequate reports from tropical countries on effective methods for soft embalming are lacking. Materials and Methods: This article details the modifications made in the Thiel embalming technique over a period of 2 years which has enabled us to preserve the anatomical features of bodies in an optimal way for longer periods in tropical conditions. This study was carried out in a tertiary care referral centre located in a tropical climate zone. A total of 13 frozen and thawed cadavers were used over a period of 2 years for developing such soft embalming technique. The efficacy of the technique was tested using these cadavers for varying types of surgical exercises on multiple occasions. Results: The conventionally described technique of Thiel embalming did not provide desired results. Hence, various modifications to this technique were instituted which helped us to get superior quality of soft-embalmed cadavers. In the final year, these cadavers were used successfully for workshops in flap dissection. Head and neck access surgery, arthroscopic and laparoscopic procedures as well as mock face and hand transplant dissections. Conclusions: The Theil embalming technique for obtaining soft embalmed cadavers, even though found to be best in many centres in the world, has not been found to be suitable to tropical weather. By modifying it, we have succeeded in developing a technique suitable to the tropical weather. This technique yields cadavers suitable for various surgical simulation exercises. This technique also allows the body to be optimally used over several months in multiple occasions. These modifications are very simple and have been described in detail enabling it to be adopted by any surgical skill laboratory in the tropical countries.